Pengaruh Kualitas Produk Health Wealth Internasional (HWI) Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening : Studi Kasus Pada Masyarakat Desa Sei Belutu Kecamatan Sei Bamban - Endang Pujianti; Suci Etri Jayanti (Digital Business Progress, 2023)
This study aims to determine "The Effect of Health Wealth International (HWI) Product Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Case Study in Sei Belutu Village Community, Sei Bamban District)". The method of determining the sample used in this study is to use the Sampling formula as many as 73 samples who are customers of HWI products in Sei Belutu Village, Sei Bamban District. Based on the results of the analysis of hypothesis 1, it staates that the first hypothesis is accepted, meaning that the Product Quality variable (X) has an effect on the Customer Satisfaction variable (Z). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is rejected, meaning that the Product Quality variable (X) has no effect on the Customer Loyalty variable (Y). Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the Customer Satisfaction variable (Z) affects the Customer Loyalty variable (Y). Based on the results of the analysis of hypothesis 4, it can be concluded that the fourth hypothesis is accepted, meaning that the customer satisfaction variable (Z) can mediate the product quality variable (X) on customer loyalty (Y).